2006
DOI: 10.1016/j.biocontrol.2006.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intraspecific competition on progeny sex ratio in Gonatocerus spp. for Homalodisca coagulata egg masses: Economic implications for mass rearing and biological control

Abstract: The eVect of the number of simultaneously ovipositing females on progeny sex ratio of three Homalodisca coagulata egg parasitoids, Gonatocerus ashmeadi, G. triguttatus, and G. fasciatus was investigated in the laboratory. When one female Gonatocerus parasitoid was present, progeny production was strongly female biased producing »1 male:8 females, 1:14 and 1:9 for G. ashmeadi, G. triguttatus and G. fasciatus, respectively. Increasing the number of simultaneous ovipositing females from 1 to 3, signiWcantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Irvin and Hoddle (2006) observed that laboratory manipulation of the adult diet for G. ashmeadi females resulted in a Ͼ370% increase in progeny production, which also supports our suggestion that egg development occurs during the adult stage of this species.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Irvin and Hoddle (2006) observed that laboratory manipulation of the adult diet for G. ashmeadi females resulted in a Ͼ370% increase in progeny production, which also supports our suggestion that egg development occurs during the adult stage of this species.…”
Section: Discussionsupporting
confidence: 86%
“…ashmeadi is a haplodiploid species (Irvin and Hoddle 2006) in which unfertilized (haploid) eggs normally develop as males and fertilized (diploid) eggs develop as females. Our results showed that the proportion of males in the F 1 generation signiÞcantly increased after their female parents were stored for Ն30 d. This indicates that the female parents were lacking viable sperm or manipulated the fertilization process as the length of storage increased.…”
Section: Discussionmentioning
confidence: 99%
“…In Anaphes nitens (Hymenoptera: Mymaridae), Santolamazza-Carbone and CorderoRivera (2003) found that at low parasitism levels, sex ratio was clearly female biased. Irvin and Hoddle (2006) reported that when only one female of the mymarid Gonatocerus spp. parasitoid was present, the progeny production was strongly female biased and that increasing the number of simultaneous females ovipositing significantly increased the male offspring.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies indicated that genetic, cytoplasmic, and behavioral factors were linked in various ways with arrhenotokous parthenogenesis (arrhenotoky) in Hymenoptera (van Wilgenburg et al 2006, Heimpel andBoer 2008). Irvin and Hoddle (2006) found that increasing the number of simultaneously ovipositing females from 1 to 3 resulted in signiÞcantly increased percentage of male offspring in three mymarid egg parasitoids of Homaladisca coagulate (Say) (Hemiptera: Cicadellidae). Three or four pairs of A. nilaparvatae adults were used in our study.…”
Section: Discussionmentioning
confidence: 98%